2024
DOI: 10.37978/tijfs.v2i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Susceptibility of Salmonella.Typhi to Ciprofloxacin, Ofloxacin and their respective Susceptibility To Nalidixic Acid

Abstract: Background: Typhoid fever is an important cause of morbidity and mortality in many parts of the world including Pakistan. Resistance to the first line anti typhoid drugs viz chloramphenicol, cotrimoxazole and ampicillin has aggravated this situation. Quinolones are currently used as the first line antityphoid drugs, instead. Fluoroquinolones are currently recommended for patients infected with Typhi. The fluoroquinolones have shown good in vitro as well as clinical activity against Typhi infections.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recommendations have been made that since these strains are susceptible to imipinems and azithromycin, the susceptible patients should be treated with these antibiotics as first line medications rather than the standard empirical treatment. 24 Not only this but the wound infection rates in the patients who had been infected with resistant strains of Salmonella Typhi were significant as compared with the patients with sensitive strains. The probable reason for this is the initial treatment with the empiric therapy failed to curb the infection and by the time culture results arrived and we started the patients on imipenem, the wound infection had already set in.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recommendations have been made that since these strains are susceptible to imipinems and azithromycin, the susceptible patients should be treated with these antibiotics as first line medications rather than the standard empirical treatment. 24 Not only this but the wound infection rates in the patients who had been infected with resistant strains of Salmonella Typhi were significant as compared with the patients with sensitive strains. The probable reason for this is the initial treatment with the empiric therapy failed to curb the infection and by the time culture results arrived and we started the patients on imipenem, the wound infection had already set in.…”
Section: Discussionmentioning
confidence: 96%
“…Pakistan is one of the few regions of the world where the extensively drug resistant Salmonella Typhihas beenreported. 23,24 The result of these resistant strains has not only posed a burden on our healthcare system but has made us as clinicians unsure if the empirical therapy that we are going to start a patient is going to get the job done effectively. 25 The data collected in this research has shown that ampicillin and Nalidixic acid are no longer nearly enough for this battle against the resistant typhoid strains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the majority of TYP-CN patients have typhoid fever, but culture avoids them (12). Therefore, serological information is trusted, and the most commonly used traditional method is broad agglutination with the advantages of low cost and easy conductivity (13).Although culture (blood, bone marrow) remains the gold standard, rapid and accurate laboratory analysis for typhoid fever is clearly needed, because the presentation is poorly identifiable and can vary significantly in patients, especially children (14,15). Widal may be misunderstood because of possible "lower" agglutinins that have not been inoculated and the immunoassay point has limited specificity only for S. typhi.…”
Section: Discussionmentioning
confidence: 99%